Pengaruh Kadar Logam Wel Terhadap Aktivitas Katalis Ni/Zeolit-Y Dalam Reaksi Hidrorengkah Minyak Bumi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Study about the effect of Ni content towards Ni/Y-Zeolite catalytic activities for hydrocracking of crude oil has been carried out. The preparation method used was ion exchange method by using the nickel nitrat solution in various concentrations. The catalyst was activated by calcinizing in a flow of nitrogen for 5 hours at 4000C and oxidizing it in the oksigen flow for 3 hours at 400Â° C, then followed by reducing in a flow of hydrogen for 3 hours at 3000 C. Catalytic activity test was conducted on fixed bed reactor for 30 minutes. The catalytic temperature was set at 3000 C and liquid phase yielded of catalytic process was analyzed by chromatographic method. The, result showed that the Ni/Y-zeolite catalysts with various Ni content had the same selectivity to C11-C12 fraction and had a different selectivity to C9-C10 fraction.